DOI: 10.17077/etd.t1t9048y
|View full text |Cite
|
Sign up to set email alerts
|

School counselors' use of the combination social storiesTM and video modeling intervention for social skills development of students diagnosed with Autism Spectrum Disorders

Abstract: Autism Disorder and related disorders such as Asperger's Syndrome and Pervasive Developmental Disorder, Not Otherwise Specified, are collectively known as Autism Spectrum Disorders (ASD). These disorders are currently the fastest growing diagnosed disorders among children and have been found in 110 in 10,000 individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
1
0
0
Order By: Relevance
“…This indicated that the intervention program proved to be effective in achieving the objectives of the study. This finding is also supported by the evidence of studies to determine the effectiveness of SLT through the use of a combination of social story strategies and video modeling in an intervention program (Gül, 2016, Halle, 2014, Cigrand, 2011, Wilkinson, 2010, Litras, Moore, & Anderson, 2010, Sansosti & Powell-Smith, 2008, Scattone, 2008. The major differences with thisstudy are: 1) the problem addressedin this study, namelysexual education, especially menstruation; 2) the subject of research in this study, a young woman of early adolescence who also has mild IDs.…”
Section: Discussionsupporting
confidence: 53%
“…This indicated that the intervention program proved to be effective in achieving the objectives of the study. This finding is also supported by the evidence of studies to determine the effectiveness of SLT through the use of a combination of social story strategies and video modeling in an intervention program (Gül, 2016, Halle, 2014, Cigrand, 2011, Wilkinson, 2010, Litras, Moore, & Anderson, 2010, Sansosti & Powell-Smith, 2008, Scattone, 2008. The major differences with thisstudy are: 1) the problem addressedin this study, namelysexual education, especially menstruation; 2) the subject of research in this study, a young woman of early adolescence who also has mild IDs.…”
Section: Discussionsupporting
confidence: 53%